(untitled) (Journal of Contemporary Philology, 2022)
Unlike the modifiers in the noun phrase, which express relatively long-lasting, more immanent features, the depictives attribute to the referent a feature which is current in the interval of the event and they are part of the sentence structure. The article analyzes the depictives in the short story collection My Husband by Rumena Buzharovska. The aim is to show what characteristics they express, what additional nuances they acquire and how they function in the information structure of the statement. First the depictives related to the subject argument are considered and then to the accusative one. In addition, the depictives not integrated in the prosodic structure of the utterance and the depictive prepositional phrases are analyzed separately. The results show that the depictives in the work most often refer to a personal subject referent and express autonomous actions and physical states, and less often physiological states, subordination in sequence and life stages. They are also carriers of varying degrees of information and show a tendency towards referents pointed out in the immediate previous context, regardless of the function of the argument to which they refer.